질감분석을 이용한 폐결핵의 자동진단 - 김대훈(Dae-Hun Kim); 고성진(Seong-Jin Ko); 강세식(Se-Sik Kang); 김정훈(Jung-Hoon Kim); 김창수(Changsoo Kim) (한국콘텐츠학회 논문지, 11(11), 2011)
There is no exact standard of detecting pulmonary tuberculosis(TB) in digital image of simple chest radiography. In this study, I experimented on the principal components analysis(PCA) algorithm in the past and suggested six other parameters as identification of TB lesions. The purpose of this study was to develop and test computer aided diagnosis(detection) method for the detection and measurement of pulmonary abnormalities on digital chest radiography. It showed comparatively low recognition diagnosis rate using PCA method, however, six kinds of texture features parameters algorithm showed similar or higher diagnosis rates of pulmonary disease than that of the clinical radiologists. Proposed algorithms using computer-aided of texture analysis can distinguish between areas of abnormality in the chest digital images, differentiate lesions having pulmonary disease. The method could be useful tool for classifying and measuring chest lesions, it would play a major role in radiologist's diagnosis of disease so as to help in pre-reading diagnosis and prevention of pulmonary tuberculosis. 결핵은 환자를 미리 발견하여 치료함으로서, 질병의 전파를 차단하여 새로운 감염자가 발생을 최소화하고, 결핵을 조기에 예방 및 진단하는 것이 중요하다. 그러므로 현재 의학에서는 디지털 의료영상을 활용하여 질병진단의 보조 수단으로서 컴퓨터자동진단시스템이 응용되고 있다. 본 연구에서 주성분 분석(PCA)과 질감분석(Texture features)의 알고리즘을 이용하여 결핵의 질병을 자동으로 판별 및 인식하였으며, 그 기준에 따라 디지털 흉부 방사선영상에서 컴퓨터자동진단의 실용화를 위한 선행연구를 하였다. 실험결과는 주성분분석을 이용한 병변 인식률은 전문의의 질병에 대한 판독률보다 낮게 나타났지만, 질감분석의 인식률은 전문의 판독결과보다 높은 병변 인식률을 나타내었다. 그러므로 제안하는 알고리즘을 활용한 컴퓨터자동진단시스템은 임상의사에게 부가적인 보조 수단으로서 예비판독 단계의 정보를 제공하여 질병의 조기진단 및 예방이 가능할 것으로 사료된다.